Pelatihan Analisis Instrumen Penilaian dan Evaluasi Kemampuan Siswa melalui Rasch Model bagi Guru SD Ma’arif NU Ngampir Pandaan Pasuruan - Kirom, Askhabul Kirom; Nurrohmatulloh, Nurrohmatulloh; Rohtih, Wiwin Ainis (LPPM Uncen, 2025)
This community service activity focuses on training in assessment instrument analysis and student ability evaluation using the Rasch Model for elementary school teachers at SD Ma'arif NU Ngampir, Pandaan, Pasuruan, with participation from eleven teachers. The main issue faced was the teachers' limited skills in using software tools to analyze test items and students' abilities comprehensively. The purpose of this activity was to enhance teachers' skills in using Winsteps software to analyze test items and assess student abilities using the Rasch Model approach. The method used was Participatory Action Research (PAR), where teachers were actively involved in every stage of the training, from planning to implementation and evaluation of the results. The training combined theoretical instruction with hands-on practice using Winsteps for data analysis. The results showed a significant improvement in the teachers' ability to use the software, especially in interpreting Rasch analysis outcomes and applying them to student learning evaluations. With this enhanced skillset, the teachers are expected to design and evaluate assessment instruments more accurately in the future.